miR-491-5p inhibits Emilin 1 to promote fibroblasts proliferation and fibrosis in gluteal muscle contracture via TGF-Beta1/Smad2 pathway - Chen, Shuai; Wu, Qiuwan; Wang, Yang; Xu, Jie; Wang, Ye; Luo, Xianyang (Physiological research, 2022)
Gluteal muscle contracture (GMC) is a chronic fibrotic disease of gluteal muscles due to multiple etiologies. Emilin 1 plays a determinant role in fibers formation, but its role in the progression of GMC remains unclear. The present study was aimed to search for the predictive role and regulatory mechanism of Emilin 1 on GMC. Here, Protein and mRNA expression of Emilin 1 were decreased in GMC tissues compared to normal muscle tissues. Using the anslysis of target prediction, Emilin 1 was observed to be a potential downstream sponge of miR-491-5p. In comparison to Emilin 1, miR-491-5p showed a aberrant elevation in GMC tissues, which was further proven to have a negative correlation with Emilin 1. The direct binding of miR-491-5p to Emilin 1 mRNA was confirmed by luciferase reporter gene assay, and miR-491-5p mimics inhibited, while miR-491-5p inhibitor promoted the protein expression and secretion of Emilin 1 in contraction bands (CB) fibroblasts. Additionally, miR-491-5p mimics promoted the expression of cyclin-dependent kinase 2 and cyclin D1 and the proliferation of CB fibroblasts, which could be reversed by Emilin 1 overexpression. Mechanistically, miR-491-5p mimics possibly activated transforming growth factor beta1 (TGF-beta1)/Smad3 signal cascade via binding to 3'-untranslated region of Emilin 1 mRNA, thereby promoting the progression of fibrosis of CB fibroblasts. Collectively, miR-491-5p inhibited Emilin 1 expression, and subsequently promoted CB fibroblasts proliferation and fibrosis via activating TGF-beta1/Smad3 signal axis. MiR-491-5p might be a potentially effective biomarker for predicting GMC, providing a novel therapeutic strategy for GMC.
Keywords: kosterní svaly; Contracture; proliferace buněk; Transforming Growth Factor beta1; Fibroblasts; Fibrosis; protein Smad2; Membrane Glycoproteins; kontraktura; lidé; messenger RNA; Muscle, Skeletal; fibroblasty; transformující růstový faktor beta1; Smad2 Protein; RNA, Messenger; mikro RNA; Cell Proliferation; MicroRNAs; membránové glykoproteiny; fibróza; Humans